DEMÉTRIOS DE FALEROS: NO LIMIAR DA POLÍTICA E DA MAGIA - Candido, Maria Regina (PHOÎNIX, 2020)
The Athenian democracy lied on a place of great honor and the democratic principles became synonimous of legitimate government. However, nobody could imagine that the Athenian people would be able to do the katádesmos magic. This magic pratice was made in curse tablets with binding spells inscribed normally on thin metal sheets, other materiais. Could also be used: ostraca or wax and even ceramic bowls.